2017
DOI: 10.12669/pjms.333.11907
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial corneal crosslinking in treatment of progressive keratoconus: 12 months’ clinical results

Abstract: Objective:The purpose of this study was to evaluate the safety and efficacy of transepithelial corneal collagen cross linking (TE-CXL) with modified riboflavin and accelerated UVA irradiance in thin corneas with pachymetry less than 400 microns at thinnest point, untreatable by epithelium off corneal collagen cross linking (CXL) in adult Pakistani population with progressive keratoconus.Methods:This quasi experimental study included twenty six eyes of 26 patients with progressive keratoconus who underwent acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…There is a growing evidence of the efficacy and safety of combining the trans-epithelial and accelerated protocols. 15,[22][23][24][25][26][27][28][29] In the present study, we evaluated the efficacy of TE-ACXL with a specific accelerated protocol (6 mW/cm 2 of UVA for 15 minutes); there is scarce published evidence. 21,23 Madeira et al had recently concluded that both TE-ACXL (6 mWcm 2 for 15 minutes) and C-CXL were similarly effective.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing evidence of the efficacy and safety of combining the trans-epithelial and accelerated protocols. 15,[22][23][24][25][26][27][28][29] In the present study, we evaluated the efficacy of TE-ACXL with a specific accelerated protocol (6 mW/cm 2 of UVA for 15 minutes); there is scarce published evidence. 21,23 Madeira et al had recently concluded that both TE-ACXL (6 mWcm 2 for 15 minutes) and C-CXL were similarly effective.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated that transepithelial and accelerated crosslinking protocols may be as effective as conventional protocols;19,22,2931 however, only a limited amount of studies have evaluated the efficacy of the TE-ACXL protocol 24,25. Until this moment, only few studies conducted in adults evaluated the efficacy of TE-ACXL; however, the protocol used was different.…”
Section: Discussionmentioning
confidence: 99%
“…Until this moment, only few studies conducted in adults evaluated the efficacy of TE-ACXL; however, the protocol used was different. In one study, the cornea was exposed to UVA irradiance of 9 mW/cm 2 for 10 minutes,25 whilst in an other, an irradiance of 45 mW/cm 2 for a total dose of 7.2 J was used 24. The first study enrolled 26 eyes with progressive keratoconus, with a mean age of 24.54±5.16 years and a significant improvement in BCVA and Kmax after 12 months of follow-up 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,18 The development of transepithelial UVA CXL is a highly active area of research, with many different methods being tested both in the laboratory and clinically. Common methods used to avoid debridement of the epithelium include the addition of chemicals such as benzalkonium chloride (BAK) to weaken epithelial tight junctions, 2,[19][20][21][22][23] the addition of vitamin E or C, 24,25 or using iontophoresis during Rf application. [26][27][28][29] Whatever the method of Rf application, however, transepithelial UVA CXL has yet to reproduce the results of traditional UVA CXL.…”
Section: Introductionmentioning
confidence: 99%